Schaum's outline of theory and problems of differential equations - Bronson, Richard
Outlines both the classic theory of differential equations and the solution procedures that practitioners favor. This guide includes several problems with worked-out solutions to help students master the basics of this linchpin of modern mathematics. It also includes more than 800 supplementary problems with answers to reinforce comprehension